Relationship between APO-A, APO-B, and C-reactive Protein with Depression in Epileptic Patients - Mirawati, Diah Kurnia; Widhianingsih, Nella Lusti; Rakhma, Titian; Subandi, Subandi; Danuaji, Rivan; Budianto, Pepi; Prabaningtyas, Hanindya Riani; Putra, Stefanus Erdana (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: Epilepsy is one of the oldest neurological disease requiring long-term treatment. Long-term use of certain anti-epileptic drugs (AED) will strongly induce cytochrome-P450 (CYP) enzyme resulting increase of homocysteine associated with risk of cerebrovascular disease and depression. The purpose of this study was to determine relationship between serum level of ApoA, ApoB, and C-Reactive Protein (CRP) with depression in epileptic patients receiving AED therapy.Subjects and Method: Respondents of this cross-sectional study were epileptic outpatients in neurology clinic Dr. Moewardi Hospital, Surakarta receiving AED therapy and met inclusion and exclusion criteria. Depression condition was evaluated by Hamilton Depression Rating Scale (HDRS). Serum level of ApoA, ApoB, and CRP of each respondent were measured from vein blood. Data were analyzed by a multiple linear regression.Results: There were 51 epileptic patients with proportional ratio between men and women (1.2:1) with age range from 18 to 59 years old. The average length of AED 92.67 months (Mean= 92.67; SD= 91.58). Average of HDRS score was 8.49. Meanwhile, average of ApoA level was 86.14 mg/dL, average of ApoB level was 47.57 mg/dL, and average of CRP level was 0.18 mg/dL. Serum level of ApoA, ApoB, and CRP increased depression (HDRS score) in epileptic patients.Conclusion: There was a statistically significant relationship between serum level of ApoA, ApoB, and CRP with depressive condition of epileptic patients receiving long-term AED treatment.Keywords: ApoA, ApoB, C-Reactive Protein, depression, epilepsyCorrespondence: Diah Kurnia Mirawati. Neurology Department of Dr. Moewardi Regional General Hospital/ Medical Faculty of Universitas Sebelas Maret, Indonesia. Email: diahkm@staff.uns.ac.id.Indonesian Journal of Medicine (2020), 05(04): 282-290https://doi.org/10.26911/theijmed.2020.05.04.03.